РАДЯНСЬКА ІСТОРІОГРАФІЯ СУСПІЛЬНО-ПОЛІТИЧНОЇ ТА КУЛЬТУРНО-ОСВІТНЬОЇ ДІЯЛЬНОСТІ УКРАЇНСЬКОЇ ЛІТЕРАТУРНОЇ ІНТЕЛІГЕНЦІЇ В ГАЛИЧИНИ Й БУКОВИНИ (кінець XIX – початок XX ст.) - (:unkn) unknown (My University, 2019)
Abstract. The article analyzes the Soviet historiography of the socio-political, cultural and educational activities of the Ukrainian literary intelligentsia of Galicia and Bukovyna of the end of XIX – the beginning of XX century. The historiographical legacy of the totalitarian era is considered, which concerns: the Ukrainian national movement in general; the role of the intelligentsia in social processes, as well as the personalities of the writers of the time. It is emphasized that the socio-political activities of the intelligentsia, including the literary, were viewed by Soviet historians through the lens of division into «revolutionary-democratic figures» and representatives of the «bourgeois-nationalist camp». It was found that Soviet researchers used a typical scheme of constructing biographies of the then «democratic writers», portraying them as «weepers» over the heavy fate of the bourgeois orders of the peasantry. And also exaggerated the influence of political and cultural figures of Russia O. Herzen, M. Chernyshevskyi, F. Dostoevskyi, Maxim Gorkyi, L. Tolstoy and others on the formation of the outlook of individual writers. At the same time, the influences of Western European thinkers and literary figures were silenced or their negative impact on the consciousness of the latter was emphasized.